PHARMACOTHERAPY POSSIBILITIES OF CARDIOVASCULAR AUTONOMOUS NEUROPATHY IN CHILDREN WITH TYPE 1 DIABETES MELLITUS AT THE PRECLINICAL STAGE - N. V. Malyuzhinskaya; I. N. Shishimorov; O. V. Magnitskaya; K. V. Stepanenko; O. V. Polyakova; G. V. Klitochenko; I. V. Petrova; S. A. Emelyanova; A. P. Skiba (Фармация и фармакология (Пятигорск))
The aim of the article is to evaluate the effectiveness of the thioctic acid preparation in the complex therapy of type 1 diabetes mellitus (T1DM) in children with cardiovascular autonomic neuropathy at the preclinical stage.Materials and methods. A design is a prospective randomized study. A clinical and instrumental examination of 64 children with preclinical stage signs of diabetic cardiovascular autonomic neuropathy (DCAN) was carried out. The cohort was divided into 2 groups: in the main and control groups, glycemic control was normalized by adjusting a dose of insulin therapy; in the main group, the children additionally received thioctic acid at the dose of 600 mg/day for 3 months. To control the effectiveness of the therapy, the technique of laser Doppler flowmetry was used.Results. After the pharmacological intervention, there was an improvement in the disease course, normalization of carbohydrate and lipid metabolism, increased vasomotor mechanisms of the regulation of the tissue blood flow due to an increase in endothelial and neurogenic kinds of activity in combination with a decrease in the intravascular tone and an increase in the effective perfusion in tissues. An increase in the heart rate variability was detected, positive dynamics of cardiovascular tests indicators according to D. Ewing, temporal (pNN50%, SDNN) and spectral indicators (VLF) were diagnosed. Achievement and maintenance of the target values of glycemic control indicators, as well as the absence of glycemic variability, turned out to be clinically significant for reducing the manifestations of neuropathy. The non-invasive technique of laser Doppler flowmetry is informative for the early diagnosis of DCAN in T1DM children.Conclusion. The carried out studies have demonstrated the effectiveness of the lipoic acid use at the dose of 600 mg/day for 3 months in the children with DCAN signs at the preclinical stage. The method of laser Doppler flowmetry for determining indications and monitoring the effectiveness of therapy makes it possible to implement a personalized approach to prescribing preventive treatment in T1DM children.